Rainha da salada - Vieira , Maria Suerlanda; Silva , Rosivam Rodrigues da; Borges, Marlene Soares da Silva; Carraro, Marcia Regina Simpioni (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2023)
>>> ver pdf